Fuel Injection System for One Cylinder Motor Cycle Engine - Sugiarto, Bambang (Makara Journal of Technology, 2004)
Fuel Injection System for One Cylinder Motor Cycle Engine. Fuel injection has been developed for many years. But its common application is limited on car’s engine. With many reason fuel injection systems in motorcycle one cylinder engine has not been widely used yet. Fuel Injection System allows the amount of fuel, injected to be controlled appropriate to engine parameters such as engine speed, amount of air inducted to cylinder, temperature, for each cycle, over the entire engine operating conditions. This fuel injection research is done to find out the Volumetric Efficiency of the intake manifold system, the amount of fuel need to be injected for each engine cycle, and the engine characteristics over variation of test conditions. This research based on Honda CB100 engine, at applied thermodynamic Laboratory of Mechanical Engineering Department, Faculty of Engineering University of Indonesia. Experiment data from this research shows the characteristics of injector duration as functions of engine speed, intake pressure, on one cylinder engine and the results of this research shows a good Volumetric Efficiency of the intake manifold designed using CFD (Computational Fluid Dynamic).